Analisis Daya Saing Pariwisata Halal di Provinsi Banten - Amrizal; Ahmad Darusalam; Erion; Gairah Sinunglingga; Koesmawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Indonesia is a country that has natural resources from a variety of cultures and ethnicities. Banten Province has beautiful and religious natural charm, making it a halal tourist destination, both locally and internationally. The aim of the research is to analyze strategies to increase the competitiveness of halal tourism in Banten Province. The research method uses a qualitative descriptive approach with in-depth interview techniques. Primary data was obtained from interviews with competent informants including the Banten Regional People's Representative Council, the Banten Provincial Tourism Office, the Indonesian Ulema Council and several Tourism Associations in Banten. and the Ministry of Tourism and Creative Economy. Qualitative data analysis using NVIVO software. The research results prove that to increase the competitiveness of halal tourism in Banten Province, the Tourism Office has taken strategic steps, including: The strategies used by the Banten provincial government in order to optimize halal tourism, namely conducting comparative studies, e-commerce or digital based tourism, Professional Human Resources Training, Infrastructure Development, Ease of Road Access